A new species of Sturnira (Chiroptera: Phyllostomidae) from the Choco forest of Ecuador - Jarrín–V, Pablo; Kunz, Thomas H. (Zootaxa, 2011)
Sturnira perla, the new species described herein, is diagnosed as an independent phylogenetic lineage in hypotheses derived from mitochondrial sequences, and shows acceptable distances in terms of genetic divergence. This description also relies on the statistical interpretation of morphological dissimilarity and overlap, and avoids qualitative judgments of character variation. Overall, this new species is characterized by a spherical skull, noticeable round and robust, with pronouncedly curved zygomatic arches. Statistical evidence that supports the discrimination of other species in Sturnira, based on external characters such as pelage coloration or number of hairs, is absent in the literature. In this sense, the geometry of the skull for this newly described species shows the sharpest morphological boundaries, relative to other closely related and sympatric taxa. This new species is likely endemic to the Choco forest, specially at its southern limits. This is an area known for its high levels of endemism. The magnitude of environmental disruption in the Choco and the potential rarity of this new species may be negatively affecting its probability of survival.